High Exoelectrogenic Biofilms Formation in Microbial Fuel Cells - Kateryna Shchurska; Liudmyla Zubchenko; Henryk Sobczuk; Yevgeniy Kuzminskyy (Innovative Biosystems and Bioengineering, 2019)
Background. Microbial fuel cells are devices in which electricity is generated by microorganisms called exoelectrogens. During the process of anaerobic respiration exoelectrogens emit electrons outside the cell. These electrons can be transferred to the anode of biofuel cell via several different mechanisms. Electricity generation in microbial fuel cells depends primarily on the electrochemical activity of the exoelectrogens present in the anode space. Nowadays, the usage of microorganisms, immobilized as biofilms on the anode, is constantly increasing. Natural sources for exoelectrogens selection such as activated sludge, biofilter biofilms, sediments of seas and rivers have a very diverse microbial composition. Therefore, it is important to immobilize relatively deficient in natural sources exoelectrogens on the anode during the biofilm formation process. The main research areas are the development of a technique for obtaining of electroactive biofilms enriched with exoelectrogens along with reduction of the period of biofilm formation process.